Biotechnology communications in Malaysia understanding the issues, influence and audience towards developing a better communication matrix / Mahaletchumy Arujanan - Arujanan, Mahaletchumy (2013)
Biotechnology became a buzzword in Malaysia with the launch of the National Biotechnology Policy in April 2005. Since then, a number of government initiatives saw heavy investment in this sector, both in terms of funding and infrastructure. Various policies were developed to serve as catalysts to propel this industry to greater heights and make Malaysia a global biotechnology player. Nevertheless, public understanding of biotechnology has not been a priority at the national level to support the enthusiasm in making biotechnology an engine for economic growth. Human capital development, public acceptance of new technology, public’s ability to make informed-decisions and ability to participate in government policies and decisions are factors that determine the success of biotechnology sector, and this can only be achieved if there is a coordinated effort in enhancing public understanding of biotechnology at the national level. A number of players from the universities, research institutes, ministries and government agencies are involved in communicating biotechnology to the public and various stakeholders but there is no integration, synergy and coherence among them. Moreover, these outreach programmes are carried out without proper understanding of public interests, perceptions and attitudes. Thus, this research attempted to map all the biotechnology communicators in Malaysia to form a better understanding of their strategies, target audiences, objectives, challenges, and proposed solutions. This was then compared against data on public interests, attitudes and perceptions which was obtained by conducting public surveys. In-depth interviews were also conducted with biotechnology communicators in the USA, UK, Singapore, the Philippines and Australia, to benchmark Malaysian biotechnology communication efforts and to adapt successful communication strategies for Malaysia. The research showed understanding of the public among communicators is lacking and communication strategies are carried out in an ad-hoc manner as institutional direction is lacking. However, although the main objectives of scientists are skewed towards branding the institutes and their research activities and commercialisation, a wide range of outreach programmes takes places, reaching out to various sectors of the publics. The missing links are the understanding of the public, national policy on biotechnology communication, synergy and integration among the communicators, trained communicators, and media support. A framework for national biotechnology communication strategy is proposed by incorporating current communication practices, addressing current challenges and shortcomings, public attitudes and interests, and international experiences. The proposed framework is expected to create a robust and effective biotechnology communication strategy for Malaysia.